Glucocorticoid induced group 2 innate lymphoid cell overactivation exacerbates experimental colitis - Feng, Bingcheng; Lin, Lin; Li, Lixiang; Long, Xin; Liu, Chao; Zhao, Zixiao; Li, Shiyang; Li, Yanqing (Frontiers in Immunology, 2022)
Abnormal activation of the innate and adaptive immune systems has been observed in inflammatory bowel disease (IBD) patients. Anxiety and depression increase the risk of IBD by activating the adaptive immune system. However, whether anxiety affects innate immunity and its impact on IBD severity remains elusive. This study investigated the mechanism by which anxiety contributes to IBD development in a murine model of acute wrap restraint stress (WRS). Here, we found that anxiety-induced overactivation of group 2 innate lymphoid cells (ILC2) aggravated colonic inflammation. Overactivation of the hypothalamic–pituitary–adrenal (HPA) axis is a hallmark of the physiological change of anxiety. Corticosterone (CORT), a stress hormone, is a marker of HPA axis activation and is mainly secreted by HPA activation. We hypothesized that the overproduction of CORT stimulated by anxiety exacerbated colonic inflammation due to the abnormally elevated function of ILC2. The results showed that ILC2 secreted more IL-5 and IL-13 in the WRS mice than in the control mice. Meanwhile, WRS mice experienced more body weight loss, shorter colon length, higher concentrations of IL-6 and TNF-α, more severely impaired barrier function, and more severe inflammatory cell infiltration. As expected, the serum corticosterone levels were elevated after restraint stress. Dexamethasone (DEX) was then injected to mimic HPA axis activation induced CORT secretion. DEX injection can also stimulate ILC2 to secrete more type II cytokines and exacerbate oxazolone (OXA) induced colitis. Blocking the IL-13/STAT6 signaling pathway alleviated colitis in WRS and DEX-injected mice. In conclusion, the overactivation of ILC2 induced by CORT contributed to the development of OXA-induced colitis in mice.